Blackcurrants: A Nutrient-Rich Source for the Development of Functional Foods for Improved Athletic Performance - Redha, Ali Ali; Siddiqui, Shahida Anusha; Zare, Reza; Spadaccini, Daniele; Guazzotti, Silvia; Feng, Xi; Bahmid, Nur Alim; Wu, Yuan Seng *; Ozeer, Fathima Zahraa; Aluko, Rotimi E. (Taylor and Francis Group, 2024)
Blackcurrants are nutrient-rich fruits with a significant amount of bioactive compounds including vitamin C and polyphenols, especially anthocyanins. The high phytochemical content of blackcurrants promotes this fruit to become a valuable functional food ingredient with varying health-promoting activities targeting different consumers including athletes. Athletes experience oxidative stress during intense exercise, which can result in inflammation and reduced exercise performance. Antioxidants such as vitamin C and polyphenols can restore the regular oxidative status of the body. Blackcurrant supplementation has shown potential ergogenic activity to improve athlete performance during high-intensity training. Clinical trials have evaluated the effectiveness of blackcurrant supplementation on exercise performance, fat oxidation, blood lactate levels, muscle fatigue, and cardiac output. Due to the rich nutritional value of blackcurrants, they can be a potential candidate for the development of functional foods targeted at the improved performance of athletes. Blackcurrants can be used as ingredients to develop functional beverages and snacks for athletes as well as gluten-free products for celiac athletes.Blackcurrant is rich in bioactive compounds that can help improve athletic performance. It can be considered a potential bioactive ingredient to develop functional foods for athletes.